Behavioral and Developmental Responses of Habrobracon hebetor (Hymenoptera: Braconidae) to Larvae of Helicoverpa armigera (Lepidoptera: Noctuidae) Inoculated With Various Concentrations of Bacillus thuringiensis var. kurstaki (Bacillales: Bacillacae). Issue 6 (24th November 2020) - Allahyari, Rahim; Aramideh, Shahram; Michaud, J P; Safaralizadeh, Mohammad Hassan; Rezapanah, Mohammad Reza
Abstract: Bacillus thuringiensis Berliner subsp . kurstaki ( Btk ) and Habrobracon hebetor Say are both biological control agents of Helicoverpa armigera Hubner. The present study evaluated their compatibility for combined application against this pest by examining the acceptability of Btk -inoculated hosts for H. hebetor females and testing for negative life-history impacts on developing progeny. Second-instar H. armigera larvae fed for 72 h on potted chickpea plants treated with three concentrations of Btk (LC15, LC35, and LC70 ) and were then used in bioassays of parasitoid development and parasitism behavior. Survival of parasitoids was significantly reduced, and immature development prolonged, on hosts fed chickpea plants treated with LC35 and LC70 Btk, but not on plants treated with LC15 Btk . Parasitoids failed to discriminate against hosts treated with LC15 or LC35 Btk in choice tests, but attacked fewer hosts treated with LC70 Btk, paralyzing and parasitizing more healthy hosts, and laying more eggs on them. In contrast, a no-choice test revealed that more hosts treated with LC35 and LC70 Btk were paralyzed compared with control or LC15 -treated hosts, but the numbers of hosts parasitized and eggs laid did not vary among Btk treatments. Thus, females required an experience with healthy hosts, as they had in the choice test, to discriminate against diseased ones. We conclude that H. hebetor and Btk are compatible for joint application against H. armigera, which could potentially improve biological control of this pest.